Constructing an information matrix for multivariate DCC-MGARCH (1, 1) method - Maleeva E. A; Kritski O. L; Mohd Hazim Mohamad Amini (Asian Research Publishing Network (ARPN), 2018)
The analytic form of Fisher Information Matrix (IM) for DCC-MGARCH (1, 1) was suggested. After that, it was applied for simplifying the general algorithm: the statistical hypothesis about constant correlation matrix usage was put forward and statistical verification was made. IM was employed for Russian share market: to do investigations the five equilibrium portfolios was compounded from four different shares in each case. Computations made showed that there are three types T1–T3 of trading days on the market and day type changing from T1 to T2 and vice versa is happening over the time moments T3. Moreover, the clustarisation effect of multivariate volatility that was investigated by scientists from all around the world in the univariate case was discovered and described.